An Examination of the Impact of the Fit between Strategic Uncertainty and Management Accounting Systems on Financial Performance - Bambang Riyanto L.S. (The Indonesian Journal of Accounting Research, 2013)
This objective of this paper is to investigate the extent to which variation in management accounting systems (MAS) attributable to strategic uncertainty was associated with performance. Management accounting system was defined to include most of its important components namely budgeting systems, scope of reporting, frequency of reporting, cost control systems and performance evaluation systems. It is hypothesized that a higher degree of fit between MAS and strategic uncertainty leads to higher performance, and a low degree of fit leads to low performance. Unlike most studies in this area, the study was conducted on a firm level, and the performance was measured financially, using return on investment.One hundred and forty nine controllers and chief financial officers from various companies in the United States participated in the study. The study reported that the effect of the fit between the total components (budgeting, cost control, performance evaluation and scope of reporting) and strategic uncertainty ROI was significant. It is consistent with the hypothesis. This finding is important given the lack of evidence about the economic performance impact of management accounting system and about the extent to which individual and total components of management accounting system interact with uncertainty to affect economic performance.